What are patients' beliefs about, and experiences of, adaptation to glasses and how does this affect their wearing habits?. (18th August 2021) - Hughes, Amy; Fylan, Fiona; Elliott, David B.
Abstract: Purpose: It is well known that some patients experience difficulties adapting to new glasses. However, little is known about what patients themselves understand of the adaptation process, and how this influences their attitudes and the decisions they make when adapting to a new pair of glasses. Nor is it understood whether these factors affect their wearing habits. Methods: We conducted four focus groups. Participants were 22 glasses wearers (mean ± SD age 43 ± 14 years, range 21–71 years) who reported they: (1) wore spectacle correction for distance vision (single vision, bifocal or progressive lenses); (2) had struggled to get used to a new pair of glasses and (3) sometimes chose not to wear their distance correction. Focus groups were audio recorded, transcribed verbatim and analysed thematically. Results: We identified three themes. Trust is about how participants' trust in their optometrist and themselves influences the likelihood of them adapting successfully to new glasses. Conflict describes how the advice patients have received about adapting to glasses can conflict with what they have experienced and how this conflict influences their expectations. Part of Me explores how participants' experiences and feelings about their glasses are important to adaptation and this includes physical, visual, emotional and behavioural aspects. Conclusions: The traditional optometric perspective of adaptation to glasses is much narrower than that held by patients, and significantly underestimates the physical, behavioural and emotional adaptation that patients must go through in order to feel fully comfortable wearing their glasses. Patients should receive significantly more information about adaptation, including symptoms that may be experienced and why these happen, practical tips to aid adaptation, and when and how to raise concerns. Patients should also receive information about the day‐to‐day effects of blur adaptation to avoid them not wearing their glasses, including for vision‐critical tasks such as driving.